2017
DOI: 10.1080/14786419.2017.1346646
|View full text |Cite
|
Sign up to set email alerts
|

Dendropsophin 1, a novel antimicrobial peptide from the skin secretion of the endemic Colombian frogDendropsophus columbianus

Abstract: In efforts to find new antimicrobial peptides (AMPs), we studied the skin secretion of the endemic Colombian frog Dendropsophus columbianus belonging to a genus that has not been investigated previously. From HPLC-fractionated secretion, we identified one peptide with slightly antibacterial activity. Its peptide sequence showed no sequence similarity to current annotated peptides. We named this novel peptide dendropsophin 1 (Dc1). Afterward, two analogues were designed (Dc1.1 and Dc1.2) to improve the cationic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…SM-985 was predicted as an α-helical peptide with an α-helix secondary structure, and the α-helical conformation has been directly linked to the antimicrobial activity (Park et al, 2000). In previous studies, many AMPs with an α-helix structure have been reported (Bonduelle, 2018;Shen et al, 2018;Triana-Vidal et al, 2018) due to the helical structure, which plays an essential role in AMP activity, whereas the α-helix secondary structure assumes an amphipathic structure and presents a precise hydrophobic portion for membrane penetration (Zelezetsky and Tossi, 2006). The 3D structural model of SM-985 was predicted using the I-TASSER server, and this model was validated with ProSA-web and MolProbity software.…”
Section: Discussionmentioning
confidence: 99%
“…SM-985 was predicted as an α-helical peptide with an α-helix secondary structure, and the α-helical conformation has been directly linked to the antimicrobial activity (Park et al, 2000). In previous studies, many AMPs with an α-helix structure have been reported (Bonduelle, 2018;Shen et al, 2018;Triana-Vidal et al, 2018) due to the helical structure, which plays an essential role in AMP activity, whereas the α-helix secondary structure assumes an amphipathic structure and presents a precise hydrophobic portion for membrane penetration (Zelezetsky and Tossi, 2006). The 3D structural model of SM-985 was predicted using the I-TASSER server, and this model was validated with ProSA-web and MolProbity software.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations inhibiting 50% of parasite growth (IC 50 ) were determined by linear regression analysis from all synthetic peptides with a concentration-response curve, and the results were expressed as the mean values ± standard deviations determined from three independent experiments. Chloroquine prepared in purified water (milli-Q grade) at 10 mM was used as the positive control [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…IC 50 values were obtained from the peptides’ concentration-response curve, and the results were expressed as the mean values ± standard deviations determined from three independent experiments. Nifurtimox prepared in DMSO at 10 mg·mL −1 was used as the positive drug control and DMSO as the negative control [ 30 , 31 , 33 , 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Guerrero-Vargas et al (110) identified novel Na + channel toxins in the venom of T. pachyurus. Furthermore, researchers from the same university isolated an antimicrobial peptide from the poison of the frog Dendropsophus colombianus (111). Dr. Santiago Ayerbe has been an active researcher on clinical toxinology and biology/ ecology of snakes.…”
Section: Other Researchesmentioning
confidence: 99%